(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the pedagogical content of developing linguistic, cultural and communicative competence of future translators is studied. Also, the requirements for speech topics, skills and qualifications of teaching foreign languages for linguistic, cultural and communicative purposes were analyzed.